The Theatre Violence, Today: Театарското насилство, денес - Lužina, Jelena; Čemerski, Ognen (Identities: Journal for Politics, Gender and Culture, 2003)
Author(s): Jelena Lužina | Јелена Лужина Title (English): The Theatre Violence, Today Title (Macedonian): Театарското насилство, денес Translated by (Macedonian to English): Ognen Čemerski | Огнен Чемерски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 89-101 Page Count: 12 Citation (English): Jelena Lužina, “The Theatre Violence, Today,” translated from the Macedonian by Ognen Čemerski, Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 2 (Winter 2003): 89-101. Citation (Macedonian): Јелена Лужина, „Театарското насилство, денес“, Идентитети: списание за политика, род и култура, т. 2, бр. 2 (зима 2003): 89-101.